Efficacy and residual toxicity of plant product extracts against Aphis gossypii and Bemisia tabaci on potato (Solanum tuberosum) - BHATNAGAR, ANUJ; KHAN, M A; LAL, M; DHAKA, R (The Indian Journal of Agricultural Sciences, 2015)
Efficacy and residual toxicity of seven plant product extracts in hexane, methanol and ethyl acetate were evaluated against cotton aphid, Aphis gossypii and whitefly, Bemisia tabaci on potato under controlled condition and efficacy of effective extracts were further evaluated under field condition at Central Potato Research Institute Campus, Modipuram during 2012-13 and 2013-14, respectively. The importance of aphids and whitefly is mainly due to their role in spread of viruses in potato crop. The highest mortality of whitefly (65.91%) was recorded in methanol bark extract of dalchini (Cinnamomum zeylanicum) followed by hexane bark extract of jatamansi (Nardostachus jatamansi) (64.3%) and methanol extract of coriander (Coriander sativus) (64.03%) after 72 hr of release as compared to control. In case of aphid, the highest mortality (44.06%) was recorded in ethyl acetate seed extract of malkangni (Celastrus paniculatus) followed by methanol extract of dalchini (40.81%) and methanol extract of jatamansi (40.72%) after 72 hr of release as compared to control. Periodic toxicity data revealed that all the tested extracts lost their toxicity within 3-4 days after spray. Hexane extract of jatamansi gave maximum PT values 53.81 and 70.3 against aphid and whitefly, respectively. Overall, hexane bark extract of jatamansi was even effective against whitefly and aphids under field condition and recorded 296.8 q tuber yield which is almost at par with methanol bark extract of dalchini (301.2 q). However, tuber yield data did not reveal significant differences among the plant product treatments with frequent spraying of plant product. This study suggested that plant product extract sprays may be included in IPM program to reduce the dependence on popular toxic chemicals to suppress aphid and whitefly population effectively on the potato crop.